The Scratch Collapse Test in patients diagnosed with Anterior Cutaneous Nerve Entrapment Syndrome (ACNES): A report of three cases. (April 2023) - Schaap, Lotte; Jacobs, Monica L.Y.E.; Scheltinga, Marc R.M.; Roumen, Rudi M.H.
Abstract: Introduction and importance: The Scratch Collapse Test (SCT) is currently used as a supportive tool diagnosing peripheral nerve neuropathies including carpal tunnel syndrome or peroneal nerve entrapment. Some patients with chronic abdominal pain suffer from entrapment of terminal branches of intercostal nerves (anterior cutaneous nerve entrapment syndrome, ACNES). ACNES is characterized by a severe disabling pain at a predictable area of the anterior abdomen. Clinical examination shows altered skin sensation and painful pinching at the area of pain. However, these findings may be subjective. Case presentation: In three female patients aged 71, 33, and 43 years with suspected ACNES, the SCT was positive when scratching over the skin of the affected nerve-ending at the abdominal wall. The diagnosis ACNES was confirmed with a local abdominal wall infiltration at the tenderpoint in all three patients. In case three, the SCT turned negative after lidocaine infiltration. Clinical discussion: ACNES was hitherto a clinical diagnosis just based on clues in medical history and physical examination. Performing a SCT in patients possibly having ACNES may additionally contribute to the diagnosis. Conclusion: The SCT may serve as an additional tool for diagnosing patients with possible ACNES. A positive SCT in patients with ACNES supports the hypothesis that ACNES is indeed a peripheral neuropathy of terminal branches of the lower thoracic intercostal nerves. Controlled research is necessary to confirm the role of a SCT in ACNES. Highlights: The Scratch Collapse Test was positive in patients with ACNES. After abdominal wall infiltration the Scratch Collapse Test became negative. The Scratch Collapse Test is a potential objective tool for diagnosing ACNES. The hypothesis that ACNES is a peripheral neuropathy was supported.